Edukasi dan Deteksi Gejala Hipertensi di Wilayah Puskesmas Maccini Sawah - Nurhayati Nurhayati; Magdalena Limbong; Andi Arniyanti; Asra Hatlah; Desriani Desriani (Universitas Muhammadiyah Manado, 2020)
Hypertension is nicknamed the silent killer because it is a disease without symptoms. This refers to a condition where blood pressure increases beyond normal limits, namely systolic pressure ≥140 mmHg and diastolic pressure <90 mmHg. Educational activities and detection of hypertension symptoms were carried out because the incidence rate was still high in the Maccini Sawah Health Center Working Area. This service is carried out with the target of people aged ≥ 40 years so that they can maintain a healthy lifestyle and have the knowledge, attitudes and skills to implement the principles of healthy living for every community. The aim of this service is to increase public awareness, understanding of prevention, lifestyle changes and increased participation in health decisions. The method for implementing this community service is education and blood pressure checks carried out simultaneously. There were 23 people who took part in this activity. The activity ran smoothly and well where the people who had been invited to take part in the education and detection of hypertension symptoms had followed it to completion with a total of 20 families participating. There are still many people who do not have their health checked at the health center. The community health center needs to carry out a door to door visit program to increase the coverage of the P2M program and reduce morbidity due to non-communicable diseases, especially hypertension.